Achnatherum inebrians Bacterial Communities Associated with Epichloë gansuensis Endophyte Infection Under Low-Concentration Urea Treatment: Links to Plant Growth and Root Metabolite - Yuanyuan Jin; Zhenjiang Chen; Kamran Malik; Chunjie Li (Microorganisms)
Despite chemical exchange often serving as the first step in plant–microbe interactions, the specialized chemical metabolites produced by grass–Epichloë endophyte symbiosis as mediators of host growth, nutrient acquisition, and modulators of the rhizosphere community under low-nitrogen conditions are areas lacking in knowledge. In this study, we investigated the plant growth-promoting effects of the Epichloë endophyte strain and identified the growth of the Epichloë strain under different types of nitrogen source treatments. In addition to the in vitro test, we evaluated growth performance for Epichloë endophyte–infected plants (E+) and Epichloë endophyte–free plants (E−) in a pot trial under 0.01 mol/L urea treatment. Seedlings from E+ and E− groups were collected to analyze the plant bacterial microbiome and root metabolites. The E. gansuensis endophyte strain was found not to produce indoleacetic acid (IAA), pectinase, or contain ferritin. The nitrogenase gene, essential for nitrogen fixation, was also absent. These results suggest that E. gansuensis endophyte strains themselves do not contain attributes to promote plant growth. Concerning N fertilization, it was observed an increase in the colony diameter of E. gansuensis strain was observed only in the NO3−-N (NN) treatment, while inhibition was observed in the urea-N (UN) treatment. E. gansuensis endophyte symbiosis significantly increased tiller number and plant dry weight. Overall, our results suggest that the E+ plants had more root forks and greater average root diameter compared to E− plants under the UN treatment. In a pot experiment using UN, data from 16S rRNA amplicon sequencing revealed that E. gansuensis endophyte infection significantly altered the bacterial community composition in shoot and root, and significantly increased Shannon (p < 0.001) and Chao 1 (p < 0.01) indexes. The relative abundance of Acidobacteriota, Actinomycetota, Cyanobacteriota, Fibrobacterota, Myxococcota, and Patescibacteria in the shoot, and Cyanobacteriota, Pseudomonadota, and Verrucomicrobiota in the root were significantly increased by E. gansuensis endophyte infection. Similarly, E. gansuensis endophyte symbiosis shifted the metabolite composition of the host plants, with the E+ plants showing a higher number of metabolites than the E− plants. In addition, co-metabolism network analysis revealed that the positive relevance between exudates and microorganisms in the root of the E+ plants is higher than that of the E− plants. These findings provide valuable insights into the knowledge of the effects of the symbiotic relationship between host plants and Epichloë endophyte on interspecific interactions of plant microbiome, beneficial for harnessing endophytic symbiosis, promoting plant growth.